Healthcare workers hydration status and performance: a scoping review - Omar B. Da’ar; Razan Alhabeeb; Farah Kalmey (Frontiers in Health Services, 2026)
Background Healthcare workers play a crucial role in providing life-saving care in high-pressure fast paced settings, where sustained alertness is critical. Adequate hydration is essential for their decision-making and timely delivery of treatment. Water intake is crucial for optimal cognitive, digestive, and cardiovascular function. The World Health Organization (WHO) emphasizes the importance of hydration in delivering quality healthcare. Therefore, this review aims to map the existing literature on healthcare workers’ hydration status and its relationship with their work performance. Methods In this scoping review, we conducted an electronic search in three databases- PubMed/PubMed Central, ScienceDirect and Google Scholar. The search was carried out between March 2023 through September 2023. Result The scoping search identified 17,799 records, of which 15 met the inclusion and exclusion criteria, and were fully reviewed ( N = 15). The result shows that dehydration affects healthcare workers significantly, with 60% reporting reduced physical performance when dehydrated during shifts. Nearly half (53%) of studies document declines in cognitive pFerformance and mood. This mental strain increased with longer shift lengths, particularly among nurses on 12-h shifts and medical residents working more than 24 h. Conclusion There is a lack of adequate studies on healthcare workers’ hydration health and its impact on performance, cognition, and mental well-being. Future research should be conducted in both cross-sectional and experimental methodologies, incorporating quantifiable measures to evaluate hydration and interventions. Countries with hot climate, such as, Saudi Arabia, should lead this research agenda, given that high temperatures could amplify the effects of inadequate hydration.